Bus rapid transit practitioner's guide (Transportation Research Board, 2007)
Introduction -- Planning framework -- Estimating BRT ridership -- Component features, costs, and impacts -- System packaging, integration, and assessment -- Land development guidelines.
At head of title: Transit Cooperative Research Program.
"Research sponsored by the Federal Transit Administration in cooperation with the Transit Development Corporation."
Keywords: Bus rapid transit -- United States -- Planning.; Bus lines -- United States -- Planning.; Local transit -- United States -- Planning.; elektronické knihy; electronic books